The Recipient in Russian Formalist Theory - bakouche, ali (El Omda in Linguistics and Discourse Analysis, 2018)
This article aims to clarify the position of the recipient in Russian Formalist theory, which emerged in the early twentieth century seeking a qualitative shift in literary studies—from focusing on the author to focusing on the text. Contextual approaches (such as historical, psychological, and social criticism, among others) were concerned with the author, their biography, psychology, and circumstances, whereas Formalism emphasized the literariness of the text. Undoubtedly, the role of the recipient was not entirely absent from the principles of Formalist theory, as is evident in some of its key concepts, such as defamiliarization and artistic perception—an aspect this article seeks to explain.